Clinical profile and management of prosthetic valve thrombosis in Tertiary cardiac Centre of Nepal, a prospective study - Manandhar, Reeju; Prajapati, Dipanker; Tamrakar, Rikesh; Bogati, Amrit; Roka, Madhu; Sherpa, Kunjang; Shrestha, Shipra; Bhandari, Shreya; Chaudhary, Taanya; Yadav, Sunil; Adhikari, Chandra Mani (Nepalese Heart Journal, 2022)
Background and Aims: Prosthetic valve thrombosis is a life- threatening complication of post-valve replacement surgeries. A number of patients present with thrombotic complications mainly due to poor anticoagulation status with irregular INR checkup especially from remote areas of Nepal. Our aim was to study the clinical profile and management of prosthetic valve thrombosis in our center. Methods: A prospective observational study of 45 patients (July 2017 – Jun 2019) admitted at Shahid Gangalal National Heart Centre, with the diagnosis of prosthetic valve thrombosis were studied. The demographic profile, clinical parameters and in hospital and 1 year outcome were analyzed. Results: Out of 45 patients, majority were female (60%) with the age 11-67 years with mean age of 34.9 ± 6.7. Twenty nine patients (64.4%) presented with sub-therapeutic INR value at admission. 46.7% patient had atrial fibrillation at the time of presentation. 88% patients presented within one week of onset of symptoms with shortness of breath being primary complaint, present in 95.6% of the patients. Forty two (86.9%) were thrombolysed with streptokinase while 3 patients underwent surgery. Valve thrombosis was most common at the mitral position 39(87%) patients. In hospital mortality was 13.3% and there were no major bleeding events or new stroke noted. Conclusion: Majority of patients with prosthetic valve thrombosis presented with a sub-therapeutic INR value and poor patients' compliance. Thrombolysis is a useful option in the management of prosthetic valve thrombosis patients especially in countries like Nepal.